(untitled) (The Pakistan Development Review, 2006)
I feel it a privilege to be asked to give the Quaid-i-Azam lecture on the occasion of the 22nd Annual Meeting of the Pakistan Society of Development Economists (PSDE). At a time when sustainability appears difficult and institutions are not finding it easy to take hold, it is a source of legitimate pride that the PSDE has been able to meet consecutively for 22 years and to bring economists together to discuss current ideas, present latest research, and to think about our country: its economy; its institutions and its future; and also to think about our profession, and the role it can play in our country, in understanding and interpreting its past and in shaping and influencing its future. And of course it is a good opportunity for us to have some fun and renew the bonds of friendship. The theme for this year’s meetings—governance—is both timely and important. And it is a tribute to the resourcefulness of the organisers, in particular the President of PSDE, Dr Nadeem Ul Haque that he has been able to attract high quality participation from the academic and policy circles of Pakistan.